2022
DOI: 10.1123/jsm.2021-0099
|View full text |Cite
|
Sign up to set email alerts
|

Becoming an Occupation? A Research Agenda Into the Professionalization of the Sport for Development and Peace Sector

Abstract: Sport for Development and Peace (SDP) has transformed from what some termed a “social movement” to an institutionalized sector with numerous organizations and practitioners involved, resulting in trends that point toward SDP becoming a recognized category of work through professional training. The purpose of this paper is to utilize theories of professions and institutional isomorphism to advance the significance and importance of thinking about SDP as a profession. Three emerging trends that point to the prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…In this way, the organization of SfD is itself always illustrative of a particular politics of development. Third, scholars have sought to understand how the SfD field or sector is organized in practice, as a burgeoning profession (Shin et al, 2020;McSweeney et al, 2021), as a series of intersecting 'facts,' (Webb and Richelieu, 2016) and/or as a loose yet intersecting and shifting amalgam of organziations and stakeholders (Svensson et al, 2020). In this sense, SfD is part of the broader sport sector but characterized in part by its organizational diversity.…”
Section: Trends and Gaps In Sport-for-development Researchmentioning
confidence: 99%
“…In this way, the organization of SfD is itself always illustrative of a particular politics of development. Third, scholars have sought to understand how the SfD field or sector is organized in practice, as a burgeoning profession (Shin et al, 2020;McSweeney et al, 2021), as a series of intersecting 'facts,' (Webb and Richelieu, 2016) and/or as a loose yet intersecting and shifting amalgam of organziations and stakeholders (Svensson et al, 2020). In this sense, SfD is part of the broader sport sector but characterized in part by its organizational diversity.…”
Section: Trends and Gaps In Sport-for-development Researchmentioning
confidence: 99%
“…As a result, there have been numerous calls to further develop educational materials and opportunities around football3 [16,18]. Likewise, other authors in SFD or related fields have identified a need for deliberate training on methods and approaches that connect sport to values or skills such as inclusion, fair play or communication [19][20][21]. Against this background, the football3-for-all project sought to further formalise and expand the reach of football3 educational materials.…”
Section: Introductionmentioning
confidence: 99%
“…The football3 MOOC follows in a growing but still limited line of online learning offers related to sport for development, including from the Swiss Academy for Development [24], the German Corporation for International Cooperation (GIZ) [25] and others [19,20]. However, sport remains an inherently physical, practical, and interactive area, and these features do not always easily translate to the online setting [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, many courses address specific sustainable development goals such as gender equality, social inclusion or environmental protection. These tools have been developed against a background of growing funding for sport-related educational materials (Moustakas 2021, McSweeney et al 2022, increased recognition of the potential for sustainability and e-learning (Otto and Becker 2019), and the overall need for distance learning due to the Covid-19 pandemic (Ebner et al 2020, Moustakas andRobrade 2022). Policymakers and researchers likewise recognise that innovative online solutions can help enhance sport's contribution to sustainable development and improve programme delivery (The Commonwealth 2021, Moustakas and Kalina 2022).…”
mentioning
confidence: 99%